2005
DOI: 10.1007/s11920-005-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of residual symptoms on outcome of major depression

Abstract: Unipolar depression should be viewed as a chronic illness with multiple phases rather than as a relapsing-remitting disorder. Incomplete remission from depression is common, with approximately one third of patients continuing to have residual depression at remission. Patients who have had a depressive episode spend more time with residual depressive symptoms than with major depression long term. The presence of residual symptomatology after an episode of depression is associated with an increased risk of short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 47 publications
0
31
0
1
Order By: Relevance
“…Furthermore, evidence shows that treatment of depression should strive to achieve full remission, often defined as scoring below a certain cut-off on a rating scales, because patients with remission have a better prognosis than those with remaining symptoms (Kennedy & Foy, 2005).…”
Section: A New Perspective On Depression Sum-scoresmentioning
confidence: 99%
“…Furthermore, evidence shows that treatment of depression should strive to achieve full remission, often defined as scoring below a certain cut-off on a rating scales, because patients with remission have a better prognosis than those with remaining symptoms (Kennedy & Foy, 2005).…”
Section: A New Perspective On Depression Sum-scoresmentioning
confidence: 99%
“…The goal of treatment is complete remission which is associated with better functioning and reduced risk of relapse. 13 While there is some evidence that people with depressive symptoms improve over time without treatment, 14,15 a significant proportion follow a chronic course with significant levels of depressive symptoms and functional continuing for several years. tricyclic antidepressants (TCAs).…”
Section: Treatments For Depressionmentioning
confidence: 99%
“…Thase: Patients who have residual depressive symptoms also tend to have a more severe course of illness, a greater burden of psychiatric and medical comorbidity, higher relapse rates, higher risk of suicide attempt, and poorer social functioning than those patients who are asymptomatic. [14][15][16] Dr. Blier: A 12-year study by Judd and colleagues 17 showed that patients with residual subthreshold symptoms, when compared with asymptomatic patients, had a more severe course of illness, had more chronic depressive episodes, and had a relapse or recurrence of the next major depressive episode more than 3 times faster.…”
Section: Dr Kellermentioning
confidence: 99%